1997
DOI: 10.1084/jem.186.5.739
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Human Neutrophil-derived Cathepsin G and Azurocidin/CAP37 as Chemoattractants for Mononuclear Cells and Neutrophils

Abstract: Macrophage infiltration into inflammatory sites is generally preceded by neutrophils. This suggests neutrophils may be the source of chemotactic factors for monocytes. To identify these putative monocyte attractants, we have systematically prepared neutrophil granules, lysed them, and sequentially purified the released proteins by several reverse phase chromatography procedures. Assays for monocyte chemotactic activity of the chromatography fractions yielded a major peak of activity associated with a protein o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
186
1
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(198 citation statements)
references
References 39 publications
6
186
1
2
Order By: Relevance
“…Chymase can cleave endothelins, producing 21-and 31-residue vasoactive peptides that are chemotactic for human monocytes, neutrophils (46), and macrophages (47). With regard to other proteases, neutrophil protease cathepsin G has also been shown to be chemotactic for human neutrophils, monocytes, and macrophages in a manner likewise dependent on enzyme activity (48,49). Injection of cathepsin G into mouse skin resulted in neutrophil and macrophage recruitment (49).…”
Section: Discussionmentioning
confidence: 99%
“…Chymase can cleave endothelins, producing 21-and 31-residue vasoactive peptides that are chemotactic for human monocytes, neutrophils (46), and macrophages (47). With regard to other proteases, neutrophil protease cathepsin G has also been shown to be chemotactic for human neutrophils, monocytes, and macrophages in a manner likewise dependent on enzyme activity (48,49). Injection of cathepsin G into mouse skin resulted in neutrophil and macrophage recruitment (49).…”
Section: Discussionmentioning
confidence: 99%
“…Since CXCR2 is expressed by a number of leukocyte subsets in addition to neutrophils, including monocytes, macrophages, dendritic cells, T cells, NK cells, and basophils (50 -52), it is possible that the CXCR2 antagonist directly inhibits ELR ϩ chemokine-induced mononuclear cell infiltration into the joint (53). Alternatively, the antagonist may directly inhibit only neutrophil chemotaxis and/or degranulation, thereby preventing the release of mediators such as defensins, CAP37/azurocidin and cathepsin G, which function as chemotactic agents for T cells and monocytes (54,55). Consistent with the latter explanation is the fact that in each of the arthritis models described, neutrophils are the first cell type to accumulate in the synovial fluid, followed sequentially by monocytes and lymphocytes (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…This is even more important, knowing that monocytes are able to herald the acquired immune response. Chertov et al [33] found azurocidin to be strongly chemotactic for monocytes and to a lesser extent, for PMN. In addition, azurocidin was proven to be chemotactic for T cells.…”
Section: Azurocidin Induces Recruitment Of Monocytesmentioning
confidence: 99%